Kepemimpinan Lokal dan Modal Sosial Dalam Pembangunan Desa Pada Masyarakat Eks Transmigrasi Desa Garantung Kecamatan Maliku Kabupaten Pulang Pisau: Local Leadership and Social Capital in Rural Development in Ex-Transmigration Village of Garantung, Sub-District Maliku, Pulang Pisau Regency - Bahrianoor Bahrianoor (Program Studi Ilmu Pemerintahan Universitas Mulawarman, 2021)
This research aims at determining the role of local leadership and social capital in rural development regarding the ex-transmigrants’ community in Garantung Village, Maliku District, Pulang Pisau Regency. The research is qualitative, with descriptive design. The result of this research shows that local leadership and social capital have significant role and function in expanding the cooperative relationship, both individually and collectively, as well as internally and externally. This cooperative relationship implies that the success of the vision of leadership can be achieved through the strength of social capital. As major aspects of social capital, ’bonding’ has a role to create togetherness and strong emotional connection, thus strengthening internal relationships; while ’bridging’ plays a role in stimulating the progress of rural development with enormous advantage for village improvement, specifically in communal resource mobilization for the benefit of Garantung Village development.